Idosas que chefiam lares multigeracionais por recoabitação: escolha ou falta de opção? - Cunha, Ubiracelma Carneiro da (2018)
The increase of human longevity is bringing a greater possibility of coexistence between the generations of the same family. Often, due to several factors that will be presented throughout this dissertation, the number of children who return to their paternal home has also increased, bringing their own children, a phenomenon known as recohabitation. With the growth of these multigenerational households, many seniors are the heads of the family and support their children, grandchildren and even great-grandchildren. This type of family arrangement can both be a source of support and mutual help, as well as of conflicts and tensions. In this context, the present study had as general objective to understand how the elderly, who are grandmothers and reside in multigenerational households, from the recohabitation by the children, experience and perceive this situation. This is a qualitative research involving nine elderly women living in the city of Vitória de Santo Antão/PE. These participants answered a sociodemographic questionnaire and a semi-structured interview. The interview was recorded, transcribed and later analyzed according to the thematic content analysis technique. The results showed that: 1) the main reason that mobilized the recohabitation was the separation/divorce of the children; 2) the majority of the elderly women had a feeling of satisfaction and conformity with the recohabitation, due to the idea that the mother should always welcome her children and grandchildren at home; 3) the return of the children and grandchildren to the maternal home caused changes both in the physical structure of the house and in the daily life of the elderly, with the addition of domestic tasks and commitments in the care of the grandchildren; 4) most of the participants considered themselves the person who establishes the norms of home functioning; 5) co-residence is not a guarantee of a friendly relationship between the generations; 6) the greatest difficulties cited were the differences regarding the education of the grandchildren, the increase of domestic responsibilities and the rebellion of the grandchildren; 7) the elderly indicated the company of their children and grandchildren as the main benefit of recohabitation; 8) expectations for themselves involve being healthy and willing to work, while for the children they have expressed a desire to remarry and for the grandchildren to continue their studies; 9) the recohabitation reflected the preference of some elderly women, due to the satisfaction of being closer to their children and grandchildren, in other cases it was perceived that it was a lack of choice, due to the feeling of "maternal obligation" to receive their children. Thus, the results highlight the need to cultivate affection bonds that support conflict resolution in this type of family arrangement, as well as strengthen intergenerational relationships.